O bibliografii pszczelnictwa polskiego - Roman Tomaszewski (Biblioteka)
The article is concerned to outline the present state o f retrospective apiculture bibliography. Bibliography in this held has not been worked out consistently and uniformly so far and still remains very patchy. The basis for the bibliography is formed by the listings made by Tadeusz Grochowski, Antoni Jakubski and Wacław Kranowski, partly complementing one another. The initiatives o f creating a comprehensive bibliography that have been taken to date were not successful. Undoubtedly, one of the reasons behind those failures is the very wide t hematic scope that has to be included. The tradition of Polish apiculture has created it own bibliographical canon. According to this canon regarding publications, basically books and periodicals published in the Polish language are only entered in bibliographies. The range of the bibliography covers thus a limited area of interest and results in its constraints and drawbacks. The article discusses the beginnings of the periodical press covering problems of apiculture and points out at the fact that there is no full and comprehensive listing of titles published in the areas historically or ethnically related to or associated with Poland. The article also recalls apicultura] periodicals that have been published locally in the Wielkopolska region. Apart from the need for compiling a full and comprehensive bibliography of publications and more important texts from periodicals as well as a complete listing o f periodicals, the absence of the subject bibliography of The Rev. Dr. Jan Dzierżoń is additionally mentioned in the article. The author proposes working out separate apicultural bibliographies covering material produced in Silesia, Western Pomerania and parts of Eastern Prussia. A modern bibliography that would record the entire output of broadly-understood Polish apicultural literature in line with current research standards still needs to be worked out.